Cyberhate on Social Media in the aftermath of Woolwich: a Case Study in Computational Criminology and Big Data - Williams, Matthew L. (The British journal of criminology, 2016)
This paper presents the first criminological analysis of an online social reaction to a crime event of national significance, in particular the detection and propagation of cyberhate on social media following a terrorist attack. We take the Woolwich, London terrorist attack in 2013 as our event of interest and draw on Cohen’s process of warning, impact, inventory and reaction to delineate a sequence of incidents that come to constitute a series of deviant responses following the attack. This paper adds to contemporary debates in criminology and the study of hate crime in three ways: (1) it provides the first analysis of the escalation, duration, diffusion and de-escalation of cyberhate in social media following a terrorist event; (2) it applies Cohen’s work on action, reaction and amplification and the role of the traditional media to the online context and (3) it introduces and provides a case study in ‘computational criminology’.